Calibration of magnification in two-dimensional low-dose full-body imaging for preoperative planning of total hip arthroplasty - Ben-Ari, Erel; Shichman, Ittai; Sissman, Ethan; Oakley, Christian; Hepinstall, Matthew; Schwarzkopf, Ran (Archives of orthopaedic and trauma surgery, 2023)
Introduction Preoperative planning of total hip arthroplasty (THA) using two-dimensional low-dose (2DLD) full-body imaging has gained popularity in recent years. The low-dose imaging system is said to produce a calibrated image with constant 1:1 magnification. However, the planning software used in conjunction with those images may introduce variations in the degree of magnification in 2DLD imaging, and this has not yet been investigated. The purpose of the present study was to quantify any variation in 2DLD image to assess the need for image calibration when using conventional planning software. Methods Postoperative 2DLD images from 137 patients were retrospectively evaluated. Only patients who underwent THA for primary osteoarthritis were included in the study cohort. The femoral head diameter was measured by two independent observers using both Orthoview™ and TraumaCad™ planning software programs. Actual sizes of the femoral head implants were extracted from surgical reports to calculate image magnification. Magnification measurement reliability was calculated with the intra-class correlation coefficient (ICC) index. Results Image magnification varied among cases (mean 133%, range 129–135%). There was no statistical difference in mean image magnification among the various implant sizes ( p = 0.8). Mean observer and inter-observer reliability was rated excellent. Conclusion THA planning with 2DLD imaging is subject to variation in magnification as analyzed with conventional planning software in this series. This finding is of paramount importance for surgeons using 2DLD imaging in preparation for THA since errors in magnification could affect the accuracy of preoperative planning and ultimately the clinical outcome.